Essential and dispensable domains of DivIVA for walled growth in filamentous Actinomycetota - Lubbers, Maarten; Bajramović, Belmin; Ongenae, Véronique; Willemse, Joost; de Bruin, Dieuwertje; Mulder, Niels; Zhang, Le; Vriesendorp, Bastienne; Barona-Gomez, Francisco; Briegel, Ariane; van Wezel, Gilles P.; Flärdh, Klas; et al. (Open biology, 2025)
The morphogenetic protein DivIVA exhibits diverse functions across bacterial phyla. In Bacillota, DivIVA is primarily involved in cell division, whereas in Actinomycetota, it plays a central role in coordinating polar growth. Due to its essentiality in Actinomycetota, gaining insight into its structural functions is challenging. We studied truncated DivIVA proteins using a unique divIVA deletion mutant in cell wall-deficient Kitasatospora viridifaciens L-forms. DivIVA comprises an N-terminal domain consisting of a coiled-coil segment bearing a membrane-targeting structure at the N-terminal end, followed by an intercoil region, a larger coiled-coil and a C-terminal domain. Deleting either the intercoil or C-terminal region affected branching. We also created a minimized variant in which both were deleted simultaneously, retaining the N-terminal domain and the second coiled-coil. Expression of this variant caused severe growth defects. Cells showed increased hyphal width, thicker cell walls and frequent tip bursting. Finally, we successfully introduced chimeric DivIVA from the unicellular actinobacterium Mycolicibacterium smegmatis with the membrane targeting domain of K. viridifaciens DivIVA, demonstrating functional conservation within the phylum. By contrast, chimeric DivIVA proteins from Bacillus subtilis could not support growth, underscoring that polar growth is encoded in Actinomycetota-specific amino acid motifs in the first and second coiled-coils. These findings enhance our understanding of the structure–function relationship for DivIVA and present new opportunities to study polar growth.
Publisher Copyright: © 2025 Royal Society Publishing. All rights reserved.
Keywords: cell wall deficiency; hyphal growth; L-forms; morphogenesis; Streptomycetaceae